Assessment of the Knowledge, Attitudes, and Practices for Optimal Oral Health among Adults in Benin City, Nigeria: A Cross-sectional Study (Update Dental College Journal, 2024)
Introduction: Oral health is crucial for overall well-being, involving the maintenance of good oral hygiene to prevent diseases. Despite global progress, gaps persist in developing countries, leading to higher oral disease prevalence. Factors such as awareness, access, cultural beliefs, and dental phobia significantly impact oral health. Knowledge, attitudes, and practices also play critical roles. Objective: To assess the knowledge, attitudes, and practices related to the oral health of adults in Benin City, Edo State.Methods: This cross-sectional study included 198 adults attending a dental outreach program in three local government areas (Ikpoba-Okha, Oredo, and Egor) in Benin City, Edo State. A sample size of 200 was determined using the Cochrane formula. A researcher-administered proforma was used for data collection, assessing socio-demographics, oral health knowledge, attitudes, and practices. A validated questionnaire was used for knowledge assessment, and a Likert scale was employed for attitude measurement. The Simplified Oral Hygiene Index (OHI-S) and the Decayed, Missing, and Filled Teeth (DMFT) index were used for clinical examination. Data were analyzed using IBM® SPSS® Statistics version 25.Results: The mean oral health knowledge, attitudes, and practices among respondents were 57.5%, 83.1%, and 55.0%, respectively.Conclusion: The study revealed fair knowledge and practices but good attitudes among respondents. Notable gaps exist in oral hygiene knowledge and practices, although the positive attitudes observed may support effective oral health promotion efforts.Update Dent. Coll. j: 2024; 14(2): 3-8